2021
DOI: 10.1002/lary.29743
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Radiation Therapy Refusal in Human Papillomavirus‐Associated Oropharyngeal Squamous Cell Carcinoma

Abstract: Objectives/Hypothesis: Human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma (OPSCC) is a distinct clinical entity with good prognosis, unique demographics, and a trend toward treatment deintensification. Patients with this disease may opt out of recommended postoperative radiation therapy (PORT) for a variety of reasons. The aim of this paper was to examine factors that predict patient refusal of recommended PORT in HPV-associated OPSCC, and the association of refusal with overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 49 publications
4
13
0
Order By: Relevance
“…In their analysis of the NCDB, Prasad et al found Black patients with HPV-associated oropharyngeal SCC were more likely to refuse PORT. 11 Similarly, Hamidi et al found that in their patient population black patients were approximately 30% more likely to refuse radiation therapy. 14 While the reasons for this discrepancy are likely multifactorial, black patients have been noted to have the lowest survival rate and highest death rate of any group.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In their analysis of the NCDB, Prasad et al found Black patients with HPV-associated oropharyngeal SCC were more likely to refuse PORT. 11 Similarly, Hamidi et al found that in their patient population black patients were approximately 30% more likely to refuse radiation therapy. 14 While the reasons for this discrepancy are likely multifactorial, black patients have been noted to have the lowest survival rate and highest death rate of any group.…”
Section: Discussionmentioning
confidence: 93%
“…Contrary to previous studies, we did not find a statistically significant difference in survival between patients who received and refused PORT. 11,14,15,19 There are multiple studies demonstrating the survival benefit of PORT. 20,21 Given the robust data in favor of radiation therapy, it is likely that the relatively small sample size of patients refusing PORT (n ¼ 73) precluded a significant difference in survival in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These variables have been defined in previous studies. 18,19 Due to the study period, all patients were staged with either the 6th or 7th edition of the AJCC staging criteria. 20 The differences between these staging criteria and the current 8th criteria for laryngeal SCCa are negligible.…”
Section: Covariatesmentioning
confidence: 99%